Waste Management Analysis at Tps 3R Mandiri Sejahtera Singosari Malang - Arna Puji Rakhmawati; Ria A.A Soemitro; I.D.A.A Warmadewanthi (IPTEK Journal of Proceedings Series, 2017)
TPS 3R Mandiri Sejahtera using reduce, reuse, and recycle principles are established by government to solve the problems of wastes in the area of the district of Singosari, Malang. According to the monitoring and evaluation processes conducted by the Directorate General of Human Settlements, Ministry of Public Works and Public Housing in 2013, it shown that there were several things at the waste management at TPS 3R had been not in accordance with the Guidelines of waste management of Directorate General of Human Settlement. This research aimed to analysis waste management at TPS 3R Mandiri Sejahtera in order to optimize the waste management. This research using descriptive Analysis. The research result showed that the function of existing waste management condition was poor, with score is 167. The result indicated that by optimizing the service up to 3% in every year until 2021, the management of TPS 3R needed to add one tricycle, eight workers for separating waste and one worker for transporting waste and to enlarge the area up to 146 m2 from 578 m2 of current area. The potential optimization processes can be conducted by increasing the coverage of services by 44.81%, the amount of waste which could be transported is 22,30 m3/day.